2021
DOI: 10.1002/ueg2.12049
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease and risk of severe COVID‐19: A nationwide population‐based cohort study in Sweden

Abstract: Background There are concerns that individuals with chronic immune‐mediated diseases are at increased risk of COVID‐19 and related severe adverse outcome, including intensive care admission or death. We aimed to explore the absolute and relative risk of severe COVID‐19 in inflammatory bowel disease (IBD). Methods This population‐based cohort study used nationwide registers in Sweden, with 67,292 individuals with a diagnosis of IBD 1969–2017 (Crohn's disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 45 publications
4
60
0
Order By: Relevance
“…Data from the SECURE registry, a prospective, international, and collaborative database, showed that the sex‐standardized mortality ratio was similar to that of the general population, 66 but updated data suggested that mortality in IBD might be higher (data not published) 67 . However, a separate multicenter analysis of 232 patients did not find differences in hospitalization or mortality risk 68,69 . In this context, the risk of severe COVID‐19 in patients with IBD (defined as ICU admission, use of mechanical ventilation, or death) seems to be driven by the same risk factors as in the general population.…”
Section: Covid‐19 In Ibdmentioning
confidence: 96%
See 1 more Smart Citation
“…Data from the SECURE registry, a prospective, international, and collaborative database, showed that the sex‐standardized mortality ratio was similar to that of the general population, 66 but updated data suggested that mortality in IBD might be higher (data not published) 67 . However, a separate multicenter analysis of 232 patients did not find differences in hospitalization or mortality risk 68,69 . In this context, the risk of severe COVID‐19 in patients with IBD (defined as ICU admission, use of mechanical ventilation, or death) seems to be driven by the same risk factors as in the general population.…”
Section: Covid‐19 In Ibdmentioning
confidence: 96%
“… 67 However, a separate multicenter analysis of 232 patients did not find differences in hospitalization or mortality risk. 68 , 69 In this context, the risk of severe COVID‐19 in patients with IBD (defined as ICU admission, use of mechanical ventilation, or death) seems to be driven by the same risk factors as in the general population. While age appears to confer additional prognostic risk as in the general population, this risk is not increased in IBD per se , 64 , 66 , 70 , 71 as observed in subjects with concomitant non‐IBD comorbidities.…”
Section: Covid‐19 In Ibdmentioning
confidence: 99%
“…Studies that reported a higher incidence are essentially three, as showed in Table 1 [ 10 , 12 , 13 ]. The study of Carparelli et al involved 600 IBD patients, both children and adults, 25 of whom were diagnosed with COVID-19 (no cases among pediatric patients).…”
Section: Is Sars-cov-2 Infection Incidence Increased In Inflammatory Bowel Diseases Affected Patients?mentioning
confidence: 99%
“…Although some studies have found a higher risk of hospitalization in IBD patients [ 10 , 11 , 13 ] ( Table 1 ), works that do not support this hypothesis are more numerous. Infection lethality was found to be 1% against 9% of the general population in a study by Allocca et al [ 20 ].…”
Section: Outcome: Which Risks For Inflammatory Bowel Diseases Affected Patients?mentioning
confidence: 99%
“…In a recent Swedish population-based study, IBD patients were at an increased risk of hospitalization for COVID-19 compared to the general population, even after adjusting for comorbidities [ 13 ]. Remarkably, the subsequent risk for intensive care unit (ICU) admission or death was comparable with a low absolute risk of severe COVID-19 in IBD patients [ 13 ]. To guide vaccination strategies against SARS-CoV-2, it is crucial to exactly delineate populations at risk for a severe course of COVID-19.…”
Section: Introductionmentioning
confidence: 99%